PENERAPAN PERPUSTAKAAN DIGITAL (DIGITAL LIBRARY) DI SMK NEGERI 1 MAJENE - M. Fhaidil Alif Hafid; Muljono Damopolii; Mardhiah Hasan (TEKNOS: Jurnal Pendidikan dan Teknologi, 2024)
In this era of globalization, progress in science and technology is happening faster than before. The development of information and communication technology in particular has had a significant influence on many aspects of life, including education. The emergence of digital libraries as a replacement for conventional libraries is one of the prominent changes in the world of education. Digital libraries offer more reliable and easier access to sources of information and knowledge in digital format. This research is an example of qualitative research that uses descriptive techniques, where observation, interviews and documentation methods are used to collect data and find sources. The realization of a digital library, according to the library manager at SMK Negeri 1 Majene, starts with the library administration procedures themselves. Planning, funding, budgeting, collection management, human resource management, performance monitoring and evaluation, analysis of management challenges, and efforts to resolve these challenges are part of digital library management.